A Management Tool for the Replication of Operating Systems in Wireless Communication Networks - Crepaldi, Luis G. [UNESP]; Digiere, Adriano R. [UNESP]; Lobato, Renata Spolon [UNESP]; Cavenaghi, Marcos Antônio [UNESP]; Lobato, Renata Spolon [UNESP] (IEEE Computer Soc, 2011)
To simplify computer management, various administration systems based on wired connections adopt advanced techniques to manage software configuration. Nevertheless, the strong relation between hardware and software makes for an individualism of that management, besides penalizing computational mobility and ubiquity. All these issues lead to degradation of scalability, flexibility and the facility to install and maintain distributed applications. This article presents an environment for centralized wireless communication network management, named WSE-OS (Wireless Sharing Environment - Operating Systems): a model based on Virtual Desktop Infrastructure (VDI) which associates virtualization techniques and safe remote access systems to create a distributed architecture as a base for a managing system. WSE-OS is capable of accomplishing the replication of operating system images using wireless communication network, besides offering abstraction of hardware to its clients, making the management more flexible and independent of wired connections. Results obtained from this work indicate that WSE-OS allows disseminating, through a single software configuration, the execution of data related to operating system images in client computers. WSE-OS can also be used as a management tool for operating systems in a wireless network.
Keywords: Virtual Desktop Infrastructure; computer management; virtual machines; remote access; Middleware for Wireless Communication